2004
DOI: 10.1016/j.devcel.2004.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Tsukushi Functions as an Organizer Inducer by Inhibition of BMP Activity in Cooperation with Chordin

Abstract: During chick gastrulation, inhibition of BMP signaling is required for primitive streak formation and induction of Hensen's node. We have identified a unique secreted protein, Tsukushi (TSK), which belongs to the Small Leucine-Rich Proteoglycan (SLRP) family and is expressed in the primitive streak and Hensen's node. Grafts of cells expressing TSK in combination with the middle primitive streak induce an ectopic Hensen's node, while electroporation of TSK siRNA inhibits induction of the node. In Xenopus embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(163 citation statements)
references
References 38 publications
(54 reference statements)
7
156
0
Order By: Relevance
“…D, phylogenetic tree analysis of NPN together with other mouse SLRP members. PRELP is proline/arginine-rich end leucine-rich repeat protein; m-TSK is mouse ortholog of tsukushi (35). consistent with its mRNA expression pattern (Fig.…”
Section: Npn Belongs To a New Class Of The Slrp Family-basedmentioning
confidence: 50%
See 1 more Smart Citation
“…D, phylogenetic tree analysis of NPN together with other mouse SLRP members. PRELP is proline/arginine-rich end leucine-rich repeat protein; m-TSK is mouse ortholog of tsukushi (35). consistent with its mRNA expression pattern (Fig.…”
Section: Npn Belongs To a New Class Of The Slrp Family-basedmentioning
confidence: 50%
“…Some of the SLRP members, e.g. asporin (33), osteoglycin (34), tsukushi (35), and podocan (36), are also known to be glycoproteins but not proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…S8 M-Q). Bone morphogenetic protein (BMP) signaling is required for the development of the CB, and we previously showed that TSK can work as a BMP antagonist during early embryonic development (13). However, the expression of TGF-β signaling components in the CB was not obviously changed in TSK −/− mice compared with WT animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TSK belongs to the group of class IV SLRPs, which includes structurally related chondroadherin (32) and nyctalopin (33), but it shares functional properties with class I SLRPs (34), including their role as BMP inhibitors (13,15). We have previously reported that TSK interacts with BMP ligands and the BMP antagonist chordin and functions as an inhibitor of BMP signaling during gastrula and neurula stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation